Development of microsatellite markers for two Australian Persoonia (Proteaceae) species using two different techniques1. (1st October 2013) - Stingemore, Jessica A.; Nevill, Paul G.; Gardner, Michael G.; Krauss, Siegfried L.
Abstract : Premise of the study: Microsatellite markers were developed and cross‐species transferability assessed for two Persoonia species to evaluate genetic diversity and population genetic structure of these broadly distributed southwest Australian tree species. Methods and Results: Microsatellite‐enriched libraries and 454 GS‐FLX shotgun sequencing were used to identity nine microsatellite loci for P. elliptica (one 454; eight cloning) and six for P. longifolia (three 454; three cloning). These loci were screened for variation in individuals from populations in southwestern Australia. In P. elliptica, observed and expected heterozygosities ranged from 0.46 to 0.93 and 0.42 to 0.88, respectively. For P. longifolia, observed and expected heterozygosities ranged from 0.04 to 0.88 and 0.04 to 0.84, respectively. Conclusions: The microsatellites identified in this study will enable the examination of population and spatial structuring of genetic diversity in P. elliptica and P. longifolia, two priority species for mine site restoration in southwestern Australia.